2009
DOI: 10.1590/s0036-36342009000200010
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity during the school day in public primary schools in Mexico City

Abstract: Objective. To quantify the physical activity (PA) of students and describe the school environment surrounding PA. Material and Methods. Between November 2005 and March 2006, in Mexico City, we conducted quantitative and qualitative observations to describe the PA and the school context. Results. Recess and physical education class (PE) were the only opportunities to participate in PA. PE occurred one time per week with a duration of 39.8±10.6 minutes which is less than national and international recommendation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
36
0
21

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 25 publications
5
36
0
21
Order By: Relevance
“…Girls living in neighborhoods that are perceived as unsafe have been found to have higher levels of overweight and obesity. 14 Carver and colleagues found that parental restriction of children's active transport and physical activity due to safety concerns resulted in lower levels of MVPA and active transport in adolescent girls. 15 Further investigation is necessary to determine whether these relationships are related to parental restriction of PA based on gender.…”
Section: Introductionmentioning
confidence: 99%
“…Girls living in neighborhoods that are perceived as unsafe have been found to have higher levels of overweight and obesity. 14 Carver and colleagues found that parental restriction of children's active transport and physical activity due to safety concerns resulted in lower levels of MVPA and active transport in adolescent girls. 15 Further investigation is necessary to determine whether these relationships are related to parental restriction of PA based on gender.…”
Section: Introductionmentioning
confidence: 99%
“…The physical activity results have been published elsewhere. [12][13] This article focuses on the healthy eating component.…”
Section: Introductionmentioning
confidence: 99%
“…At the organizational level, in addition to the physical activity intervention published elsewhere, 12,26 strategies to improve offerings of healthy food and water and to reduce opportunities to eat and availability of non-healthy food and beverages were selected.…”
mentioning
confidence: 99%
“…Though it has been widely documented that physical activity is positively related to the reduction of obesity and cardiovascular risk [3][4][5][6], actual physical activity practice is very far from international recommendations in the Mexican children population. It has been reported for Mexico, that in the school environment there are few opportunities to do physical exercise of moderate or vigorous intensity and that the physical activity level decreases as school grades increment [7,8]. Lack of physical areas and environments that promote physical activity in school and nonschool spheres, may explain part of this problem [8].…”
Section: Introductionmentioning
confidence: 99%